Cement-free magnesium castable and use method thereof
Through the design of cementless magnesium castable, aluminium-based metal microcapsules and magnesium sand particles are used to form a high-density structure, which solves the problem of the degradation of existing magnesium castables at high temperatures and achieves excellent slag corrosion resistance and thermal shock resistance, extending service life.
Patent Information
- Application Number
- CN202411278868.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-12
AI Technical Summary
The existing magnesium castables have deteriorated performance at high temperatures, insufficient slag corrosion resistance and thermal shock resistance, short service life, and commonly used cement bonding agents will introduce impurities to reduce the high-temperature mechanical properties.
It uses cementless magnesium castable, consisting of 60-80 parts of magnesium sand particles, aluminum-based metal microcapsules and water reducing agent. The aluminum-based metal microcapsules are prepared by reduction reaction and heat treatment, and magnesium sand particles and magnesium sand fine powder are added. Use sodium pyrophosphate, sodium tripolyphosphate or sodium hexametaphosphate as water reducers to form high density and mesh structures to improve early strength and high temperature performance.
It realizes high performance of cementless magnesium castable at high temperatures, slag corrosion resistance and thermal shock resistance, long service life, and does not generate low melting point phases, which improves the refractory and high temperature performance of castable.
Smart Images

Figure CN119191821A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, and in particular to a cement-free magnesia castable and a use method thereof. Background Art
[0002] Magnesium castables with magnesia as the main raw material have the advantages of high refractoriness, high load softening temperature, good resistance to alkaline slag corrosion, good compatibility with molten steel, and low pollution to molten steel due to oxygenation, which meets the requirements of clean steel smelting. In modern industrial production, the quality and performance requirements of magnesium castables are getting higher and higher. The binder for magnesium castables determines the quality, microstructure and high-temperature performance of magnesium castables to a certain extent. At present, the bonding system is developing in the direction of "purification" and "stabilization". "Purification" means that the binder should not introduce impurities as much as possible, because impurities are usually not conducive to high-temperature performance. "Stabilization" is to minimize the damage to the material structure caused by the volatilization or decomposition of the binder.
[0003] Magnesia refractory castables initially used calcium aluminate cement binder, which can obtain sufficiently high early strength and excellent construction performance at low ambient temperatures. The minerals in cement are mainly calcium aluminate (CA) and calcium dialuminate (CA2), and generally contain a very small amount of calcium dodecaaluminate (C 12 A7). After the castable is mixed with water, the calcium aluminate minerals CA, CA2, C 12 A7 reacts with water, and the staggered growth of hydration products causes the castable to gradually solidify and harden. Although cement has high early strength and excellent construction performance, the use of cement also brings some adverse effects: on the one hand, the castable is combined with water removal when heated, which destroys the structure and causes the material to peel off or even burst; on the other hand, the CaO introduced by cement easily reacts with SiO2, MgO, Al2O3 and other materials in the castable or the use environment to form low-melting products, thereby reducing high-temperature mechanical properties and slag resistance. This limits the use temperature and life of cement-bonded castables.
[0004] Magnesium oxychloride cement is used as a binder for magnesium castables. Magnesium oxychloride cement is a gel material formed by the ternary components of MgO-MgCl2-H2O, which has the advantages of fast coagulation, high strength, good elasticity and easy molding. The high-temperature decomposition product of magnesium oxychloride cement is active MgO. Using it as a binder for magnesium refractory castables has the advantages of not introducing harmful substances, high load softening temperature of the material, good slag resistance and low price. However, the disadvantage is that after heat treatment at 1100℃, the flexural strength of the castable decreases significantly. This is mainly because the magnesium oxychloride cement gel undergoes dehydration and decomposition reaction during the heating process to transform into MgO, and the gel structure is destroyed, thereby greatly weakening the performance of the castable.
[0005] Polyphosphates (mainly sodium polyphosphate) are used as binders for monolithic refractory materials, among which sodium tripolyphosphate and sodium hexametaphosphate are common binders for magnesium castables. Sodium tripolyphosphate is dissolved in water to form sodium monohydrogen phosphate and sodium dihydrogen phosphate. These two compounds react with MgO to form sodium magnesium phosphate to produce a binding effect. When it is used as a binder for magnesium castables, the castable hardens faster, has higher strength, and has good thermal shock stability. When sodium tripolyphosphate is heated, polymerization occurs that helps to improve the strength of the material, and the phase change does not cause the green body structure to become loose. Therefore, the material combined with it has higher strength from room temperature to medium temperature. However, after the liquid phase appears at high temperature, the hot strength of the castable is reduced.
[0006] When sodium hexametaphosphate is used as a binder, it is hydrolyzed into sodium dihydrogen phosphate (NaH2PO4) when it comes into contact with water. NaH2PO4 and alkaline earth metal oxides such as magnesia are made into castables, and they can react to form Mg(H2PO4)2 at room temperature. After drying, Mg(H2PO4)2 quickly forms MgHPO4, which has high adhesion and can make the castable harden quickly. Mg(H2PO4)2 and MgHPO4 are condensed at about 500℃ to form magnesium polyphosphate [Mg(PO3)2] n and [Mg2(P2O7)] n , which further improves the strength of the combination, and has a relatively high strength in a relatively large temperature range before the liquid phase appears (before 800℃). However, after the liquid phase appears at high temperature, the hot strength of the castable decreases.
[0007] At present, magnesium castables mainly use SiO2 powder binder, and use MgO and SiO2 powder to react with water to produce MgO-SiO2-H2O gel to generate bonding strength. The castables of this bonding system have the following characteristics: (a) SiO2 powder particles are small, have a large specific surface area, and are spherical. After introduction, it can improve the fluidity of the castable and increase the density; (b) No impurities such as CaO and Na2O are introduced. As the temperature rises, MgO and SiO2 can react to form high-melting-point phase forsterite (M2S), which improves the high-temperature performance of the material; (c) The gel contains less bound water, and can slowly dehydrate within a large temperature range during heating, with a low weight loss rate. Therefore, the castable has good anti-burst performance, which is conducive to the rapid baking of the castable. The MgO-SiO2-H2O bonding system is used in a series of prefabricated parts such as small and medium-sized ladle castables, tundish slag retaining walls and impact plates due to its good use effect, high cost performance and relatively stable performance. However, too much silicon oxide can cause the material to produce too much liquid phase (magnesium silicate) at high temperatures, seriously affecting its performance at high temperatures and causing significant "oxygenation" in the molten steel.
[0008] For example:
[0009] (1) The Chinese patent application number CN201510298745.5, "Calcium aluminate cement combined with aluminum-magnesium castable and its preparation method", uses calcium aluminate cement as a binder and titanium dioxide / calcium carbonate / magnesium oxide powder as a composite additive. Titanium dioxide promotes sintering, magnesium oxide reacts with corundum to form spinel, and calcium carbonate is converted into highly active calcium oxide at high temperatures, which greatly improves the strength of the aluminum-magnesium castable. However, due to the large amount of cement added, the cement contains a small amount of CaO. CaO reacts with Al2O3 and SiO2 in the castable at high temperatures to form low-melting-point substances, which will seriously reduce the performance of the castable at high temperatures.
[0010] (2) Chinese patent application number CN201110251826.1, “Amide binder for cement-free castable”, contains acrylamide, N-N'-methylenebisacrylamide, ammonium persulfate, tetramethylethylenediamine or tetramethylethylenediamine complex, which is dissolved in water and added to the castable, effectively solving the problem of surface powdering of the castable and greatly improving the flexural strength and compressive strength of the castable. However, the amide binder releases harmful gas (NO3) during use.
[0011] (3) The Chinese patent application number CN201210216100.9, “A kind of aluminum-magnesium refractory castable and its preparation method”, uses a mixture of hydrated alumina powder and pure aluminate cement as a bonding system. During high-temperature use, magnesium-aluminum spinel will be generated in situ inside the castable, and microcracks will be generated inside the castable, which can buffer the thermal stress generated during rapid cooling and heating, and has strong thermal shock resistance. However, the amount of pure aluminate cement added is large, and more liquid phase will be generated at high temperature, resulting in poor high-temperature performance of the material.
[0012] (4) The Chinese patent application number CN200710052468.5, “A Lightweight Cement-free Aluminum-Magnesium Castable Material and Its Preparation Method”, produces porous ceramics as aggregates, mainly with magnesium oxide and silicon oxide powder as binders. The binder can form a good chain network with water, making the matrix part more dense, avoiding the disadvantages of calcium aluminate cement as a binder, such as the use temperature cannot be too high, easy to produce structural peeling and poor slag resistance. However, too much SiO2 in the system can cause the material to produce too much liquid phase at high temperature, seriously affecting its performance at high temperature, limiting the use temperature of aluminum-magnesium materials, and bringing significant "oxygenation" to the molten steel.
[0013] (5) Chinese patent application number CN201210134262.8, “A silica sol-bonded magnesium tundish preform and its manufacturing method”, uses silica sol as a binder. SiO2 particles in the silica sol are evenly distributed in the preform, forming a dense and uniform structure with strong resistance to slag erosion and molten steel erosion. However, there are still problems such as long curing time and low strength after baking. Summary of the invention
[0014] The purpose of the present invention is to address the above-mentioned deficiencies of the prior art and provide a cement-free magnesium castable and a method for using the same. The castable has a certain initial strength, excellent high temperature performance, excellent slag erosion resistance and thermal shock resistance, long service life, and can be widely used in tundishes, ladles and other parts.
[0015] A cement-free magnesium castable of the present invention, the castable is composed of aggregate, matrix material and water reducing agent;
[0016] The aggregate is 60-80 parts of magnesia particles;
[0017] The base material is:
[0018]
[0019] The preparation method of the aluminum-based metal microcapsule is:
[0020] S1. placing aluminum powder or aluminum-based alloy powder in a metal compound solution for reduction reaction, stirring for a period of time, depositing metal nanoparticles on the surface of the aluminum powder or aluminum-based alloy powder, adding magnesium salt to the solution, stirring for 30 minutes, filtering and drying to obtain a microcapsule precursor;
[0021] S2, heat-treating the microcapsule precursor at 150° C. to 500° C. in air and then cooling it naturally to obtain aluminum-based metal microcapsules.
[0022] Furthermore, the particle size of the aluminum powder or aluminum-based alloy powder is ≤74 μm, and the aluminum-based alloy powder contains Si and Fe, and the Si content is less than 40 wt%.
[0023] Furthermore, in step S1 of the method for preparing aluminum-based metal microcapsules, the reduction reaction is carried out at 40 to 60° C. and stirred for 30 to 60 minutes.
[0024] Furthermore, in step S1 of the method for preparing aluminum-based metal microcapsules, the metal compound solution is a ferric chloride solution or a nickel chloride solution, and the metal nanoparticles are nano-Fe or nano-Ni particles.
[0025] Furthermore, in step S1 of the method for preparing aluminum-based metal microcapsules, the magnesium salt is one of magnesium nitrate, magnesium oxalate and magnesium carbonate.
[0026] Further, the magnesia particles include:
[0027] 18-25 parts of magnesia particles with a particle size less than 5 mm and greater than or equal to 3 mm,
[0028] 24-30 parts of magnesia particles with a particle size less than 3 mm and greater than or equal to 1 mm,
[0029] 18-25 parts of magnesia particles with a particle size less than 1 mm and greater than 0.1 mm;
[0030] The MgO content of the magnesia fine powder is ≥96wt%, the particle size of the magnesia fine powder is ≤40μm, and the magnesia fine powder is one of fused magnesia and sintered magnesia.
[0031] Furthermore, the water reducing agent content is 0.1-0.4% of the sum of the aggregate and the matrix material, and the water reducing agent is one of sodium pyrophosphate, sodium tripolyphosphate, sodium hexametaphosphate and sodium silicate.
[0032] A method for using the cement-free magnesium castable as described above comprises mixing a water reducer which accounts for 0.1 to 0.4% of the sum of the aggregate and the matrix material with the matrix material to obtain a premixed matrix material; uniformly stirring the aggregate and the premixed matrix material, adding water which accounts for 3 to 4% of the sum of the aggregate and the matrix material, stirring for 1 to 3 minutes, and obtaining a slurry; pouring the slurry into a mold, vibrating and molding, and curing for 1 to 3 days.
[0033] Due to the adoption of the above technical solution, compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The aluminum-based metal microcapsules added to the cement-free magnesium castable of the present invention have good sphericity, can improve the fluidity of the castable, require less water, and make the castable structure more compact.
[0035] 2. The aluminum-based metal microcapsules added to the cement-free magnesium castable of the present invention contain boehmite, metal nanoparticles (Fe or Ni) and nano-MgO on their surfaces. Nano-MgO has a large specific surface area and high activity. When mixed with water, it forms a network structure and has coagulation properties, which improves the early strength of the cement-free castable, and does not generate a low melting point phase at high temperatures, thereby improving the refractoriness and high temperature performance of the magnesium castable. Metal nanoparticles can be used as catalysts to promote the formation of magnesium-aluminum spinel whiskers / fibers.
[0036] 3. The aluminum-based metal microcapsules added to the cement-free magnesium castable of the present invention rupture at a temperature greater than 600°C, exposing the metal aluminum, which combines with oxygen to form nano-Al2O3 and Al2O3 whiskers in situ, resulting in micro-expansion to fill pores and improve the density of the material.
[0037] 4. In the cement-free magnesia castable of the present invention, magnesia particles, magnesia fine powder and magnesium oxide in aluminum-based metal microcapsules react with nano-Al2O3 at high temperature in situ to generate magnesia-alumina spinel whiskers / fibers, which greatly improves the strength of the castable. The micro-expansion generated by the in-situ reaction to generate magnesia-alumina spinel whiskers / fibers is beneficial to filling pores, reducing pore diameters, preventing slag penetration, and improving the corrosion resistance and penetration ability of the castable. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The microstructure of the cement-free magnesia castable of the present invention after calcination at 1500°C for 3h. DETAILED DESCRIPTION
[0039] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.
[0040] Example 1
[0041] The invention discloses a cement-free magnesium castable material, which consists of aggregate, matrix material and water reducing agent.
[0042] The aggregates are:
[0043] 18 parts of magnesia particles with a particle size less than 5 mm and greater than or equal to 3 mm;
[0044] 30 parts of magnesia particles with a particle size less than 3 mm and greater than or equal to 1 mm;
[0045] 18 parts of magnesia particles with a particle size less than 1 mm and greater than 0.1 mm.
[0046] The base material is:
[0047]
[0048]
[0049] The preparation method of the aluminum-based metal microcapsule is:
[0050] S1. Place aluminum powder or aluminum-based alloy powder in a metal compound solution, perform a reduction reaction at 60°C, stir for 60 minutes, deposit metal nanoparticles on the surface of the aluminum powder or aluminum-based alloy powder, continue to add magnesium nitrate to the solution, stir for 30 minutes, filter and dry to obtain a microcapsule precursor.
[0051] S2, heat-treating the microcapsule precursor at 300° C. in air and then cooling it naturally to obtain aluminum-based metal microcapsules.
[0052] The method for using the cement-free magnesium castable is as follows: 0.4% of the water reducing agent of the sum of the aggregate and the matrix material is mixed with the matrix material to obtain a premixed matrix material; the aggregate and the premixed matrix material are mixed evenly with a cement mortar mixer, and 3% of water of the sum of the aggregate and the matrix material is added for wet mixing, and stirred for 1 to 3 minutes to obtain slurry; the mixed slurry is poured into a mold, vibrated to form, and cured for 1 to 3 days.
[0053] The cement-free magnesium castable prepared in Example 1 of the present invention was heat treated at 1100°C for 3 hours and tested to have a room temperature flexural strength of 15 MPa, a room temperature compressive strength of 80 MPa, an apparent porosity of 14%, and a bulk density of 2.99 g / cm 3 After heat treatment at 1500℃×3h, the test results show that the room temperature flexural strength is 20MPa, the room temperature compressive strength is 160MPa, the apparent porosity is 12%, and the volume density is 3.10g / cm 3 .
[0054] The process parameters of Examples 1-4 are shown in Table 1 and Table 2:
[0055] Table 1
[0056]
[0057] Table 2
[0058]
[0059] The performance results of the cement-free magnesium castables of Examples 1-4 are shown in Table 3:
[0060] Table 3
[0061]
[0062] Figure 1 The microstructure of the cement-free magnesium castable material of the present invention after calcination at 1500°C for 3 hours. Figure 1 It can be seen that after calcination at 1500℃×3h, a large number of magnesia-alumina spinel whiskers / fibers are generated in the matrix. These whiskers / fibers are interwoven into a network structure, which has a reinforcing and toughening effect.
[0063] For matters not mentioned above, the prior art applies.
[0064] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A cement-free magnesia castable, characterized in that: The castable is composed of aggregate, matrix material and water reducing agent; The aggregate is 60-80 parts of magnesia particles; The base material is: The preparation method of the aluminum-based metal microcapsule is: S1. placing aluminum powder or aluminum-based alloy powder in a metal compound solution for reduction reaction, stirring for a period of time, depositing metal nanoparticles on the surface of the aluminum powder or aluminum-based alloy powder, adding magnesium salt to the solution, stirring for 30 minutes, filtering and drying to obtain a microcapsule precursor; S2, heat-treating the microcapsule precursor at 150° C. to 500° C. in air and then cooling it naturally to obtain aluminum-based metal microcapsules.
2. The cement-free magnesia castable according to claim 1, characterized in that: The particle size of the aluminum powder or aluminum-based alloy powder is ≤74 μm, and the aluminum-based alloy powder contains Si and Fe, with the Si content being less than 40 wt%.
3. The cement-free magnesia castable according to claim 1, characterized in that: In step S1 of the method for preparing aluminum-based metal microcapsules, a reduction reaction is carried out at 40 to 60° C. and stirred for 30 to 60 minutes.
4. The cement-free magnesia castable according to claim 1, characterized in that: In step S1 of the method for preparing aluminum-based metal microcapsules, the metal compound solution is a ferric chloride solution or a nickel chloride solution, and the metal nanoparticles are nano-Fe or nano-Ni particles.
5. The cement-free magnesia castable according to claim 1, characterized in that: In step S1 of the method for preparing aluminum-based metal microcapsules, the magnesium salt is one of magnesium nitrate, magnesium oxalate and magnesium carbonate.
6. A cement-free magnesia castable according to claim 1, characterized in that: The magnesia particles include: 18-25 parts of magnesia particles with a particle size less than 5 mm and greater than or equal to 3 mm, 24-30 parts of magnesia particles with a particle size less than 3 mm and greater than or equal to 1 mm, 18-25 parts of magnesia particles with a particle size less than 1 mm and greater than 0.1 mm; The MgO content of the magnesia fine powder is ≥96wt%, the particle size of the magnesia fine powder is ≤40μm, and the magnesia fine powder is one of fused magnesia and sintered magnesia.
7. A cement-free magnesia castable according to claim 1, characterized in that: The water reducing agent content is 0.1-0.4% of the sum of the aggregate and the matrix material, and the water reducing agent is one of sodium pyrophosphate, sodium tripolyphosphate, sodium hexametaphosphate and sodium silicate.
8. A method for using the cement-free magnesia castable according to any one of claims 1 to 7, characterized in that: The water reducing agent of 0.1-0.4% of the sum of the aggregate and the matrix material is mixed with the matrix material to obtain a premixed matrix material; the aggregate and the premixed matrix material are stirred evenly, and water of 3-4% of the sum of the aggregate and the matrix material is added, and stirred for 1-3 minutes to obtain a slurry; the slurry is poured into a mold, vibrated and formed, and cured for 1-3 days.
Citation Information
Patent Citations
Non-cement light alumina magnesia cast material and its prepn process
CN101066855A
Amide binder for no cement castable material
CN102417319A
Silica sol combined magnesium tundish prefabricated member and manufacturing method thereof
CN102659430A
Aluminum-magnesium refractory castable material and preparation method thereof
CN102718513A
Calcium-aluminate-cement-bound aluminum magnesium castable and preparation method thereof
CN104909774A
